2006
DOI: 10.1108/09685220610690817
|View full text |Cite
|
Sign up to set email alerts
|

On security preparations against possible IS threats across industries

Abstract: PurposeModernized information systems (IS) have brought enterprises not only enormous benefits, but also linked information threats. Most enterprises solve their IS security‐related problems using technical means alone, and focus on technical rather than managerial controls, which may imply potential crises. This study examines whether the security preparation of firms matches the severity of IS threats they perceive in developing countries, especially in issues concerning “people” and “administration”. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…Finally, results suggest that the strategies adopted by the managers did not have any significant impact on the enhanced level of cyber-security. While our findings were contradictory to extant studies that successfully examined organisational strategies to influence the maturity levels of cyber-security (Chang and Yeh, 2006; Pérez-González et al , 2019; Nassimbeni et al , 2012; Tang and Liu, 2015), we posited that the conflicting results could be due to the lack of visibility of these strategies among the respondents in our study. Additionally, the lack of any significant positive effect of IT security strategies on the enhanced level of cyber-security in organisations could be due to the choice of the industry sectors for our study, i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Finally, results suggest that the strategies adopted by the managers did not have any significant impact on the enhanced level of cyber-security. While our findings were contradictory to extant studies that successfully examined organisational strategies to influence the maturity levels of cyber-security (Chang and Yeh, 2006; Pérez-González et al , 2019; Nassimbeni et al , 2012; Tang and Liu, 2015), we posited that the conflicting results could be due to the lack of visibility of these strategies among the respondents in our study. Additionally, the lack of any significant positive effect of IT security strategies on the enhanced level of cyber-security in organisations could be due to the choice of the industry sectors for our study, i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…The strategies adopted by the senior management, in general, align with the business strategies of the organisation (Chang and Yeh, 2006; Nassimbeni et al , 2012). For our study, we have categorised the strategies adopted by senior management towards an enhanced level of cyber-security in the organisation, into the following five streams: clear vision , institutionalised IT security governance , risk management controls , reward policy and information sharing .…”
Section: Background Literature and Hypothesis Developmentmentioning
confidence: 99%
“…With our theoretical model in mind, we selected a case based on previous research in information security. Prior research has found that organizations in the financial services, telecommunication and utilities sectors present rich cases for information security research due to their greater focus on information security threats and protection [35]. We chose an organization from the financial services sector.…”
Section: Methodsmentioning
confidence: 99%
“…Effective ISS management is not a standalone activity, but should be founded on a well-developed security strategy (Seeholzer, 2012). ISS security strategies should be balanced with and support business strategies (Chang & Yeh, 2006;McFadzean, Ezingeard, & Birchall, 2011). Organizations must be able to assess the effectiveness of ISS and communicate its value to the organization (McFadzean et al, 2011).…”
Section: Iss Managementmentioning
confidence: 99%